2021
DOI: 10.12982/vis.2021.045
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the effects of enrichment on stereotypic and non-stereotypic stabled horses

Abstract: Our preliminary study investigated: 1) differences of general behaviors between stereotypic (male, n=2, ST) and non-stereotypic (male, n=2, NST) stabled horses 2) the different reactions to enrichment items (hay nets, bedding straw and yoga ball) between ST and NST horses. The frequency of general behaviors, stereotypic behaviors and the reactions to enrichment items were recorded. The results showed that there was a significantly different frequency of ingestion, locomotion, standing alert, investigation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…During the observation, the female sun bear did not often get chance to use BC when the male sun bear using, therefore, BC might be needed to add one more, in order to let every sun bear has equal change to use it. Huo et al (2021) found that the different reactions to enrichment items occurred between stereotypic and non-stereotypic horses. Unfortunately, this study focused on a single bear, we did not compare the time budget between stereotypic and non-stereotypic sun bear, the future study should be needed.…”
Section: The Response To Enrichment Toolsmentioning
confidence: 96%
See 2 more Smart Citations
“…During the observation, the female sun bear did not often get chance to use BC when the male sun bear using, therefore, BC might be needed to add one more, in order to let every sun bear has equal change to use it. Huo et al (2021) found that the different reactions to enrichment items occurred between stereotypic and non-stereotypic horses. Unfortunately, this study focused on a single bear, we did not compare the time budget between stereotypic and non-stereotypic sun bear, the future study should be needed.…”
Section: The Response To Enrichment Toolsmentioning
confidence: 96%
“…It might because feeding enrichment related feeding or foraging motivation (Vickery and Mason, 2004). Moreover, the nonedible items are not useful for enrichment purposes when horses are appropriately reared (reviewed by Huo et al, 2021). During the observation, the female sun bear did not often get chance to use BC when the male sun bear using, therefore, BC might be needed to add one more, in order to let every sun bear has equal change to use it.…”
Section: The Response To Enrichment Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Huo et al (2023) claimed that the captive sun bear would be more interested in an edible enrichment tool compared with using other types, which could reduce the frequency of pacing. Both stabled non-stereotypic horses individually and in groups performed significantly more item-directed behaviors towards edible items (Huo et al, 2021). The enrichment items (cone and takraw: a rattan ball) used for the monitor lizards, which were made of plastic, easily to find and low cost.…”
Section: Enrichmentmentioning
confidence: 99%
“…The welfare of captive reptiles has been the object of various studies (Hayes et al,1998;Warwick et al, 2013;Bashaw et al, 2016;Pasmans et al, 2017;Hoehfurtner et al, 2021;Nagabaskaran et al, 2021), but a large part of their biological, physiological and behavioral characteristics is still not known (Scarpellini, 2018), not to mention the welfare of the reptile's requirements in captivity which are not always met, due in part to an apparent lack of awareness of their needs (Lambert et al, 2019). Enrichment has been documented to improve the welfare of mammals (Huo et al, 2021;Huo et al, 2023), birds, turtles and tortoises, but other taxa have not been well-studied (Swaisgood and Shepherdson, 2005;Burghardt, 2013, as cited in Bashaw et al, 2016. Giving captive animals the opportunity to interact with objects in a "playful" manner is often considered a method of environmental enrichment.…”
Section: Introductionmentioning
confidence: 99%